The superlattice structure and self-adaptive performance of C–Ti/MoS2 composite coatings. Issue 5 (1st April 2020) - Li, Li; Lu, Zhaoxia; Pu, Jibin; Wang, Haixin; Li, Qiang; Chen, Shibo; Zhang, Zhifeng; Wang, Liping
Abstract: To improve the self-adaptability of MoS2 coating in different environments, the coatings were doped with functional C and Ti by unbalanced magnetron sputtering system. The clear superlattice structure with minimal modulation period was investigated by High Resolution Transmission Electron Microscope (HRTEM). The co-doped coatings have better mechanical properties due to the special structure and the formation of C–Mo, Ti–S and Ti–O bonds, and better lubrication performance in both high humidity and vacuum than those of the single-doped ones. The doped Ti not only facilitates the formation of the MoS2 (002) basal plane, but also improves the oxidation resistance of the composite film. The degree of friction-induced graphitization on the wear tracks and the quality of transfer films on the wear scars are key factors affecting the lubrication performance of the composite film. In the high-humidity environment, the reasonable doping elements can promote the formation the high-quality transfer film by interacting with H2 O water molecules, which will benefit the lubrication of the coating better. Our findings deepen the understanding of MoS2 composite coating and provide a new solution for improving the self-adaptability of the coating.